Health service communication in monitoring toddler growth and development in the New Normal at Posyandu Hidup Baru Desa Kaong, Kecamatan Upau, South Kalimantan, Indonesia - Migang, Yena Wineini; Migang, Evan Kristianus (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
At the Toddler Posyandu or Posyandu Balita, the health workers and mothers and toddlers are possible to meet, and they may communicate together to monitor toddlers growth and development. This photo essay records our health service communication in monitoring toddler growth and development in the New Normal at Posyandu Hidup Baru Desa Kaong, Kecamatan Upau, South Kalimantan, Indonesia. The activities include counseling, height and weight checking for toddles, and immunization. The visits cannot be done virtually, since we must directly provide examination of nutritional status, immunization, counseling and others monitoring to the mothers and toddlers following the standard protocols, and not all mothers of toddlers have the measuring devices. Since the checking and monitoring have been done during the Covid 19 pandemic, posyandu must apply health protocols when communicating and providing health service to the mothers and toddlers. Thus, all participants presented at the posyandu will not get infected with covid 19, and the toddler growth and development can be monitored regularly.